2005
DOI: 10.1523/jneurosci.1314-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Selectivity of Output Neurons Innervating an Identified, Sexually Isomorphic Olfactory Glomerulus

Abstract: The antennal lobe (AL) of insects, like the olfactory bulb of vertebrates, is characterized by discrete modules of synaptic neuropil called glomeruli. In some insects (e.g., moths and cockroaches), a few glomeruli are sexually dimorphic and function in labeled lines for processing of sensory information about sex pheromones. Controversy still exists, however, about whether projection (output) neurons (PNs) of glomeruli in the main AL are also narrowly tuned. We examined this critical issue in the AL of the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 76 publications
3
48
0
Order By: Relevance
“…The c3HA-related propionate and butyrate evoked fewer action potentials at lower spike frequencies in PNs of both males and females [Reisenman et al (2005) When an extended panel of 14 plant odors was tested in two female G35-PNs at a relatively high and an intermediate concentration, respectively, the authors confirmed a preference for c3HA in both neurons (higher net number of spikes and longer duration of excitation). However, c3HA selectivity is less pronounced when other response parameters (the peak instantaneous spike frequency and the delay of the response onset) are comparatively analyzed [Reisenman et al (2005), their The study by Reisenman et al addresses one of the key issues in olfactory coding and processing: the dynamic sensitivity range used by individual uniglomerular output neurons to integrate odor information. Thus far, imaging studies of odor-evoked neuronal activity in the antennal lobe (or the vertebrate olfactory bulb) have failed to provide definite answers to this question because available methods lack single-cell resolution and are frequently limited to reporting presynaptic activity.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The c3HA-related propionate and butyrate evoked fewer action potentials at lower spike frequencies in PNs of both males and females [Reisenman et al (2005) When an extended panel of 14 plant odors was tested in two female G35-PNs at a relatively high and an intermediate concentration, respectively, the authors confirmed a preference for c3HA in both neurons (higher net number of spikes and longer duration of excitation). However, c3HA selectivity is less pronounced when other response parameters (the peak instantaneous spike frequency and the delay of the response onset) are comparatively analyzed [Reisenman et al (2005), their The study by Reisenman et al addresses one of the key issues in olfactory coding and processing: the dynamic sensitivity range used by individual uniglomerular output neurons to integrate odor information. Thus far, imaging studies of odor-evoked neuronal activity in the antennal lobe (or the vertebrate olfactory bulb) have failed to provide definite answers to this question because available methods lack single-cell resolution and are frequently limited to reporting presynaptic activity.…”
mentioning
confidence: 79%
“…Subsequent to electrophysiological characterization, a given PN was injected with a fluorescent dye to confirm neuronal identity by confocal imaging in brain sections and three-dimensional reconstruction of the antennal lobe ( Having established postrecording staining as a valid tool to determine PN identity in Manduca, the authors focused on individual odor response characteristics of G35-PNs. When the moths' antennae were challenged with a panel of several host plant odors, G35-PNs from both sexes preferentially responded to cis-3-hexenyl acetate (c3HA), typically displaying triphasic alternations of membrane hyperpolarization and action potential firing [Reisenman et al (2005) How selective are G35-PNs for c3HA stimulation? To address this issue, Reisenman et al first screened two structural derivatives of c3HA for their stimulatory capacity.…”
mentioning
confidence: 99%
“…glomeruli present in both sexes (e.g. Heinbockel et al, 1999;Guerenstein et al, 2004;Reisenman et al, 2005). Stimulation with (-)-linalool, by contrast, only evoked a hyperpolarisation (Fig.…”
Section: Electrophysiological Experimentsmentioning
confidence: 96%
“…Moreover, linalool participates in mediating oviposition behaviour in M. sexta, with (+)-linalool and (-)-linalool, respectively, producing attraction and repellence for oviposition in normal females (Reisenman et al, 2010). Cis-3-hexenyl-acetate was used because we have shown that this odorant activates projection neurons in a sexually isomorphic glomerulus that neighbours the LFGs, which has similar effects in both male and female neurons (Reisenman et al, 2005). Single odour compounds were diluted to a concentration of 1:500 in odourless mineral oil (Sigma-Aldrich, St Louis, MO, USA); 50 ml of solution was applied to a disc of filter paper and inserted into a 20 ml stimulus syringe (Reisenman et al, 2004).…”
Section: Electrophysiological Experimentsmentioning
confidence: 99%
“…It is known that increasing odor concentrations recruit increasing numbers of glomeruli [86] and the activity of the projection neurons within the AL [87,88,89]. From the behavioral point of view, increasing the synapses of the local inhibitory neurons makes gases repulsive and to change the number of excitatory synapses makes odorants attractive [90].…”
Section: The Formation Of Memories In the Mushroom Bodiesmentioning
confidence: 99%